Faith in development: mixed-method studies on worldviews and religious styles - Streib, Heinz; Hood, Ralph W. Jr. (BiUP General, 2024)
How has faith developed in the US and German societies across the last decades? In a three-wave longitudinal investigation of faith development, this study presents the changes of worldview and meaning-making that people associate with their religious, spiritual, agnostic and atheist identifications. For almost two decades, research teams in Chattanooga (USA) and Bielefeld (Germany) have invited and re-invited hundreds of people to participate in a personal interview and to answer an extensive questionnaire in order to better understand the reasons and the consequences of their continuity or discontinuity in religious, spiritual, or non-theistic faith